ANALYSIS OF THE EFFECTIVENESS OF SKILL TRAINING AND MOTIVATION ON THE GROWTH OF ENTERPRENEURIAL INTEREST ON MEMBERS OF SETIA BHAKTI WANITA EAST JAVA WOMEN COOPERATIVE - Suwangsih, Iwang (International Business Management - Universitas Ciputra, 2020)
Abstract The purpose of this study is to describe and analyze whether training skill or short course which had been done by woman cooperative can grow entrepreneurial interest on woman cooperative’s members. The sampling technique used was simple random sampling with a simple size of 100 respondents to formula Isaac and Michael. The variable is training skill, motivation and entrepreneurial interest. The result of this study concluded that training skill variable simultaneously and partially have significant effect on entrepreneurial interest of woman cooperative’s members.